The influence of self-control training on self-regulated learning in Merdeka Belajar Kampus Merdeka (MBKM) collage students - Malahati, Fildzah; Rohmadani, Zahro Varisna; Winarsih, Tri (International Journal of Health Science and Technology, 2025)
This study aims to examine the effectiveness of self-control training on self-regulated learning in UNISA collage students involved in the MBKM program. This research employs a quantitative method with an experimental design, specifically a pre-test post-test control group design. The criteria for subjects in this study are: 1) UNISA students in Yogyakarta participating in the MBKM program in 2024; and 2) willingness to complete the entire training process. The sample of the study was taken using a purposive sampling technique. The number of participants was 14 students who were participating in MBKM, consisting of 12 females and 2 males aged between 20 and 23 years old. Data collection involves using quesionare of the Self-Regulated Learning (SRL) likert scale, observations, and training evaluations conducted according to the Self-Control Training module. Data analysis methods include paired sample t-test to examine differences between pre-test and post-test conditions within a single group and independent sample t-test to assess differences between two groups (experimental and control). Based on the research results, a 2-tailed significance value of 0.013 < 0.05 indicates a significantly positive effect of the intervention. Based on the research findings, a two-tailed significance value of 0.013 was obtained, which is less than 0.05, indicating a significant positive effect of the intervention. Consequently, the Self-Control Training has a positive impact on the enhancement of Self-regulated Learning among MBKM students. The data analysis process was conducted using SPSS version 23 for Windows.